Facilitators and barriers influencing utilization of services provided by community midwives in district Thatta, Pakistan: a qualitative exploratory study - Bakhtawar M. Hanif Khowaja; Anam Shahil Feroz; Sarah Saleem (BMC, 2022)
Abstract Background To address the issue of high maternal mortality, the Government of Pakistan initiated a community midwifery program in 2006 to provide skilled birth attendance to women living in rural areas. Despite a large investment in the community midwifery program, research evidence from rural districts of Pakistan suggests that the utilization of maternal and newborn services through community midwives is very low. This exploratory study aimed to understand the facilitators and barriers influencing community midwives' services utilization in district Thatta. Methods A qualitative study was conducted in the rural district Thatta, Pakistan. Key-informant interviews (KIIs) were conducted with district officials of the Health department (Thatta), Maternal and Newborn Child Health Program, and Midwifery Association of Pakistan (MAP). In-depth Interviews (IDIs) were conducted with midwifery students who were currently enrolled in the midwifery program of the district; trained community midwives providing services in district Thatta, and trained community midwives not continuing their profession. IDIs were also conducted with community women to explore their views about the scope of midwifery practice and the factors influencing the utilization of community midwives' services in district Thatta, Pakistan. Data were analyzed using qualitative thematic analysis. Results A total of 25 interviews (KIIs = 5; IDIs = 20) were conducted. Two overarching themes were identified: (I) community midwives' skills and competencies; and (II) ownership and supportive supervision. The major hindering factors for community midwives' service utilization included deficiencies in community midwives' training particularly in clinical hands-on training, lack of ownership of community midwifery program, and lack of service structure by the CMWs regulatory body. Conclusion The study has identified serious gaps in the CMWs program at the level of training and supervision of midwives in Pakistan. The study has also identified factors related to the training of CMWs that could facilitate the program in the context of Pakistan and similar settings.